Tasyri’ pada zaman rasulullah - Kamilia, Syalaisha Kholila (Maliki Interdisciplinary Journal, 2024)
The Shari’a during the time of the Prophet started when the revelation from Allah came down in the form of the Koran which came down when the Prophet was alone in the cave of Hira. To be precise, on the 17th of Ramadhan, 13 years before the Hijrah. Before the Apostle was sent, the conditions of the Arab nation were very diverse both in terms of economics, politics and legislation. From a social aspect, the Arab nation is a nation that cannot write, does not have knowledge and also has no morals. The dominant religion at that time was idol worship. Every tribe had a statue placed next to the Kaaba. From an economic aspect, the majority of Arabs herd goats. They cannot make ends meet so they often steal/rob. The Tasyri stage during the time of the Prophet had two periods, namely the Mecca period and the Medina period. The Makkah period lasted 13 years from the time the Prophet was sent. Meanwhile, the Medina period lasted for 10 years from when the Prophet moved to Mecca until he died. The sources of law used at that time were the Al-Quran and Hadith. Then, there were many differences in ijtihad during the time of the Prophet, according to the Asy’ariyah of Sunnah experts and the majority of Mu’tazilah were of the opinion that the Prophet should not perform ijtihad alone in accordance with the text of the Al-Quran, Surah An-Najm verses 3 and 4. Second opinion came from the ushul ulama who stated that the prophet could make ijtihad in every case and affair.